Enhancement of acute lung injury related to bacterial endotoxin by components of diesel exhaust particles. Issue 7 (1st July 2003) - Yanagisawa, R; Takano, H; Inoue, K; Ichinose, T; Sadakane, K; Yoshino, S; Yamaki, K; Kumagai, Y; Uchiyama, K; Yoshikawa, T; Morita, M
Abstract : Background: Diesel exhaust particles (DEP) synergistically aggravate acute lung injury related to lipopolysaccharide (LPS) in mice, but the components in DEP responsible for this have not been identified. A study was undertaken to examine the effects of the organic chemicals (DEP-OC) and residual carbonaceous nuclei (washed DEP) derived from DEP on LPS related lung injury. Methods: ICR mice were divided into experimental groups and vehicle, LPS, washed DEP, DEP-OC, washed DEP+LPS, and DEP-OC+LPS were administered intratracheally. The cellular profile of the bronchoalveolar lavage (BAL) fluid, pulmonary oedema, lung histology, and expression of proinflammatory molecules and Toll-like receptors in the lung were evaluated. Results: Both DEP-OC and washed DEP enhanced the infiltration of neutrophils into BAL fluid in the presence of LPS. Washed DEP combined with LPS synergistically exacerbated pulmonary oedema and induced alveolar haemorrhage, which was concomitant with the enhanced lung expression of interleukin-1β, macrophage inflammatory protein-1α, macrophage chemoattractant protein-1, and keratinocyte chemoattractant, whereas DEP-OC combined with LPS did not. Gene expression of Toll-like receptors 2 and 4 was increased by combined treatment with washed DEP and LPS. The enhancement effects of washed DEP on LPS related changes were comparable to those of whole DEP. Conclusions: These results suggest that the residual carbonaceous nuclei of DEP rather than the extracted organic chemicals predominantly contribute to the aggravation of LPS related lung injury. This may be mediated through the expression of proinflammatory cytokines, chemokines, and Toll-like receptors.